Book Reviews (Journal of Finance, 1990)
Book reviewed in this article: Share Markets and Portfolio Theory (2nd ed) . Edited by R. BALL, P. BROWN, F. J. FINN, and R. R. OFFICER. An Introduction to Options and Futures . By DON M. CHANCE. Money, Banking, and Credit . By DWIGHT M. JAFFEE. The Economics of Uncertainty and Information . By JEAN‐JACQUES LAF‐FONT.